The Implementation of Planning and Budgeting Redesign System in National Nuclear Energy Agency - Nata Wijaya (BATAN, 2021)
BATAN is presently applying the RSS concept of planning and budgeting redesign systems to prepare a work plan and budget document for 2021. This concept changes the nomenclature of programs, activities, and outputs that are input into the KRISNA. It also influences the substance of programs, activities, and outputs of each budget. The implementation of the RSPP concept is expected to strengthen the money follow program concept for the successful implementation of programs and activities in accordance with statutory regulations